Determinants of relative and absolute concentration indices: evidence from 26 European countries - Ásgeirsdóttir, Tinna Laufey (BioMed Central, 2013)
INTRODUCTION: The aim of publicly-provided health care is generally not only to produce health, but also to decrease variation in health by socio-economic status. The aim of this study is to measure to what extent this goal has been obtained in various European countries and evaluate the determinants of inequalities within countries, as well as cross-country patterns with regard to different cultural, institutional and social settings. METHODS: The data utilized in this study provides information on 440,000 individuals in 26 European countries and stem from The European Union Statistics on Income and Living Conditions (EU-SILC) collected in 2007. As measures of income-related inequality in health both the relative concentration indices and the absolute concentration indices are calculated. Further, health inequality in each country is decomposed into individual-level determinants and cross-country comparisons are made to shed light on social and institutional determinants. RESULTS: Income-related health inequality favoring the better-off is observed for all the 26 European countries. In terms of within-country determinants inequality is mainly explained by income, age, education, and activity status. However, the degree of inequality and contribution of each determinant to inequality varies considerably between countries. Aggregate bivariate linear regressions show that there is a positive association between health-income inequality in Europe and public expenditure on education. Furthermore, a negative relationship between health-income inequality and income inequality was found when individual employee cash income was used in the health-concentration measurement. Using that same income measure, health-income inequality was found to be higher in the Nordic countries than in other areas, but this result is sensitive to the income measure chosen. CONCLUSIONS: The findings indicate that institutional determinants partly explain income-related health inequalities across countries. The results are in accordance with previously published theories hypothesizing social mobility as the explanation for differences in health-income inequalities between countries and higher health-income inequality could be a result of lower income inequality.